2012
DOI: 10.5402/2012/658470
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Patterns of Escherichia coli Isolates from Hospitals in Kumasi, Ghana

Abstract: Nosocomial infections are infections acquired by a patient as a result of treatment in a hospital or healthcare service providing center and symptoms occurs within a short period of hospitalization. The study was to determine the antibiotic resistance patterns of Escherichia coli isolated from Kumasi-South, Tafo and Suntreso Hospitals, Kumasi, Ghana. Total of 600 swabs samples from the hospitals were collected between January and June, 2010. The isolates were identified using morphological and biochemical mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 9 publications
4
18
1
Order By: Relevance
“…The only Klebsiella isolate compared to other isolates had an overall high antibiotic susceptibility but the high susceptibility to Gentamicin (100%) and Ciprofloxacin (100%) is not in agreement with 17.39% and 41.3% respectively of Ullah et al, 2009 and 35.4% and 62.5% respectively of Abdullah et al, 2013. The antibiogram of the 10 E. coli isolates showed low susceptibility of 20% to Ampicillin which is similar to 11.6% reported by Niranjan et al, 2014 and 10.3% reported by Duredoh et al, 2012. However, Susceptibility of Ciprofloxacin and Gentamicin showed a 50% susceptibility which is close to 70% and 53.6% respectively as reported by Duredoh et al, 2012. The antibiogram of Pseudomonas with 9 isolates reveal susceptibility to Streptomycin 3(33%); Ciprofloxacin 6(66%); Gentamicin 4(44%); Nalidixic acid 3(33%); Pefloxacin 7(77%); Augmentin 1(11%); Septrin 6(66%); Ampicillin 2(22%); Cephalosporin 2(22%) and Ofloxacin 7(77%).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The only Klebsiella isolate compared to other isolates had an overall high antibiotic susceptibility but the high susceptibility to Gentamicin (100%) and Ciprofloxacin (100%) is not in agreement with 17.39% and 41.3% respectively of Ullah et al, 2009 and 35.4% and 62.5% respectively of Abdullah et al, 2013. The antibiogram of the 10 E. coli isolates showed low susceptibility of 20% to Ampicillin which is similar to 11.6% reported by Niranjan et al, 2014 and 10.3% reported by Duredoh et al, 2012. However, Susceptibility of Ciprofloxacin and Gentamicin showed a 50% susceptibility which is close to 70% and 53.6% respectively as reported by Duredoh et al, 2012. The antibiogram of Pseudomonas with 9 isolates reveal susceptibility to Streptomycin 3(33%); Ciprofloxacin 6(66%); Gentamicin 4(44%); Nalidixic acid 3(33%); Pefloxacin 7(77%); Augmentin 1(11%); Septrin 6(66%); Ampicillin 2(22%); Cephalosporin 2(22%) and Ofloxacin 7(77%).…”
Section: Resultssupporting
confidence: 85%
“…However, Susceptibility of Ciprofloxacin and Gentamicin showed a 50% susceptibility which is close to 70% and 53.6% respectively as reported by Duredoh et al, 2012. The antibiogram of Pseudomonas with 9 isolates reveal susceptibility to Streptomycin 3(33%); Ciprofloxacin 6(66%); Gentamicin 4(44%); Nalidixic acid 3(33%); Pefloxacin 7(77%); Augmentin 1(11%); Septrin 6(66%); Ampicillin 2(22%); Cephalosporin 2(22%) and Ofloxacin 7(77%). The percentage susceptibility is in agreement with studies by Golshani et al, 2012 with Gentamicin having 40%.…”
Section: Resultssupporting
confidence: 84%
“…George et al (2012) determined the antibiotic resistance patterns of Escherichia coli isolated from patients in selected hospitals in Kumasi, Ghana and reported that Escherichia coli isolates (28.6-46.4%) were resistant to gentamicin, ciprofloxacin and ceftriaxone while 14.4-47.4% gave intermediate responses. This study found 13.33% resistance to gentamicin, 2.22% resistance to ciprofloxacin and 26.67% Table 1 Table Cro 1 (Namboodiri et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the misuse of antibiotics in food-animal production is one of the most important factors contributing to the global surge and spread in antibiotic resistance [12]. Several studies have reported high level of antibiotic resistant bacteria isolated from patients visiting healthcare facilities in Ghana [13][14][15][16][17] and even among the healthy populace [18]. These reports show an increase in antibiotic resistance in both commensals and pathogenic bacteria and this raises a concern to public health system.…”
Section: Introductionmentioning
confidence: 99%